Functional Analysis of Genes GlaDFR1 and GlaDFR2 Encoding Dihydroflavonol 4-Reductase (DFR) in Gentiana lutea L. Var. Aurantiaca (M. Laínz) M. Laínz. (10th January 2022) - Yu, Tingting; Han, Guojun; Luan, Zhihui; Zhu, Changfu; Zhao, Jinghua; Sheng, Yanmin
Abstract : Anthocyanins are important pigments for flower color, determining the ornamental and economic values of horticultural plants. As a key enzyme in the biosynthesis of anthocyanidins, dihydroflavonol 4-reductase (DFR) catalyzes the reduction of dihydroflavonols to generate the precursors for anthocyanidins (i.e., leucoanthocyanidins) and anthocyanins. To investigate the functions of DFRs in plants, we cloned the GlaDFR1 and GlaDFR2 genes from the petals of Gentiana lutea var. aurantiaca and transformed both genes into Nicotiana tabacum by Agrobacterium -mediated leaf disc method. We further investigated the molecular and phenotypic characteristics of T1 generation transgenic tobacco plants selected based on the hygromycin resistance and verified by both PCR and semiquantitative real-time PCR analyses. The phenotypic segregation was observed in the flower color of the transgenic tobacco plants, showing petals darker than those in the wild-type (WT) plants. Results of high-performance liquid chromatography (HPLC) analysis showed that the contents of gentiocyanin derivatives were decreased in the petals of transgenic plants in comparison to those of WT plants. Ours results revealed the molecular functions of GlaDFR1 and GlaDFR2 in the formation of coloration, providing solid theoretical foundation and candidate genes for further genetic improvement in flower color of plants.